FREQUENCY OF ELECTROLYTES IMBALANCE IN CHILDREN WITH ACUTE WATERY DIARHHEA (The Research of Medical Science Review, 2024)
Introduction: Abnormal electrolyte levels accompanied by acute diarrhea are frequently observed. Electrolytes, which are ionized molecules present in both the bloodstream and various bodily tissues and cells, play a crucial role in maintaining proper pH levels in the body by balancing sodium, potassium, and bicarbonate concentrations. Children under the age of two face a heightened risk of contracting diarrheal illnesses due to unhealthy feeding practices and inadequate weaning, particularly in socioeconomically disadvantaged populations. Thus, the objective of this investigation was to determine the prevalence of significant electrolyte irregularities in diarrheal conditions within this specific age group, aiming to promptly identify and correct such imbalances. Methodology: The research was conducted at the Department of Pediatrics SUGHRA SHAFI MEDICAL COMPLEX, PAKISTAN, spanning from December 10, 2023, to June 9, A total of 176 children, who presented with acute diarrhea, were included in this study. Anthropometric measurements, including weight and height, were performed. Upon the child's admission, aseptic techniques were employed to collect 2ml of whole blood during the insertion of intravenous cannulation, prior to the administration of intravenous fluids. This blood sample was then sent to the laboratory. The presence of hyper/hyponatremia and hyper/hypokalaemia was determined. All the gathered data were entered and analysed using SPSS v25. Furthermore, the data were stratified based on age, gender, and the duration of diarrhea to identify any influential factors. Post- stratification, a Chi-square test was conducted, with a significance level set at p≤0.05. Results: Total 176 children with acute diarrhea were included. Among 176 children, 105(59.7%) were males and 71(40.3%) were females. Age range in this study was from 1 to 24 months with mean age of 12.91 months. Mean serum sodium level was 136.3mEq/l and mean serum potassium level was 3.8mEq/l. Out of 176 children, 97(55.1%) had serum electrolytes abnormalities.Conclusion: Significant alterations in serum electrolyte levels were observed among patients afflicted with diarrhea. The foremost anomaly detected was hypokalemia, which was subsequently followed by hyponatremia. Henceforth, it is crucial to closely monitor the levels of serum sodium and serum potassium in children experiencing acute diarrhea, particularly those who are below the age of 24 months.